2016
DOI: 10.1111/cen.13028
|View full text |Cite
|
Sign up to set email alerts
|

Concerns about the safety of patients with diabetes insipidus admitted to hospital

Abstract: combination with human Chorionic Gonadotropin (hCG) in inducing increased testicular volume and spermatogenesis in adult men with hypogonadotropic hypogonadism who remain azoospermic when treated with hCG alone. In: ClinicalTrials.gov [Internet]. [cited 2015 September]. Available from: http://clinicaltrials.gov/show/NCT01709331 6 Vermeulen, A., Verdonck, L. & Kaufman, J.M. (1999) A critical evaluation of simple methods for the estimation of free testosterone in serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Results of a retrospective audit of patients hospitalized with central DI showed that desmopressin treatment had been missed or delayed in 88% of admissions and that 35% of patients consequently developed dysnatraemia [79]. This was attributed to a lack of understanding of the critical nature of desmopressin amongst clinical staff [80].…”
Section: Management Of DI For Nonspecialists (With a Focus On Emergency Management In Hospitals)mentioning
confidence: 99%
“…Results of a retrospective audit of patients hospitalized with central DI showed that desmopressin treatment had been missed or delayed in 88% of admissions and that 35% of patients consequently developed dysnatraemia [79]. This was attributed to a lack of understanding of the critical nature of desmopressin amongst clinical staff [80].…”
Section: Management Of DI For Nonspecialists (With a Focus On Emergency Management In Hospitals)mentioning
confidence: 99%
“…A paediatric endocrinologist should be contacted as soon as possible after admission. Given the potential risk of morbidity and mortality as a result of failure to adhere to simple principles, in particular with out-of-hours and unplanned admissions, we recommend that a hospital alert system for patients with DI is established in line with the recommendations from NHS England 1 2…”
Section: Discussionmentioning
confidence: 99%
“…It is important to ascertain whether a patient on desmopressin is also on steroid replacement medication 2. Cortisol is required for the excretion of free water.…”
Section: Special Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…-In 2018, the Society for Endocrinology (SfE) published guidelines on in-hospital management of central DI 15 . This report was prompted by a study of patients hospitalized with central DI, which showed that desmopressin treatment had been missed or delayed in 88% of admissions, and that 35% of patients consequently developed dysnatraemia 16 . This was attributed to a lack of understanding of the critical nature of desmopressin amongst clinical staff 17 .…”
Section: Acute Infection With Suspected or Confirmed Covid-19mentioning
confidence: 99%